Protective Effect of Emblica officinalis Against S.typhimurium Through its Antioxidant Activity - Khan, K.H. (Recent Research in Science and Technology, 2010)
Typhoid is a major public health problem caused by Salmonella typhi. SalmonellaÂ typhimurium (S. typhimurium) causes an invasive disease in mice that has similarity with human typhoid. The antibiotics used got resistant to the bacteria and has side effects while vaccine developed has little scope against this disease. In this study antioxidant activity of fruits of Emblica officinalis was explored against the oxidative stress generated by S. typhimurium in mice. Animals pretreated with EO500 for a period of 30 days followed by challenged with 50000 (CFU) of S. typhimurium exhibit a decrease in Xanthine oxidase activity by 36% and increase in glutathione peroxidase and glutathione reductase activity by 37% and 38% respectively as compared to mice infected with same doses of S. typhimurium. Â The study confirmed the lowering of oxidative stress in mice by this drug and can be used in typhoid.